Maulana Ashraf ’Ali Thanawi’s. Perfecting women. Bihishi Zewar. Trad. parcial y coment. de Barbara Daly Metcalf. Berkeley: University of California Press, 1992. xv, 436 p. - Castañeda Reyes, José Carlos; Metcalf, Barbara Daly (Estudios de Asia y África, 1999)
-